2021
DOI: 10.1186/s12873-021-00528-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of QSOFA and sirs scores for the prediction of adverse outcomes of secondary peritonitis among patients admitted on the adult surgical ward in a tertiary teaching hospital in Uganda: a prospective cohort study

Abstract: Background SIRS and qSOFA are two ancillary scoring tools that have been used globally, inside and outside of ICU to predict adverse outcomes of infections such as secondary peritonitis. A tertiary teaching hospital in Uganda uses SIRS outside the ICU to identify patients with secondary peritonitis, who are at risk of adverse outcomes. However, there are associated delays in decision making given SIRS partial reliance on laboratory parameters which are often not quickly available in a resource … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…The SIRS score, derived from the number of SIRS criteria met in terms of inflammatory activity [ 122 ], has been used to predict outcomes in septic and trauma patients [ 126 , 127 ]. Hokari et al found that patients with aSAH with a higher SIRS score on day 3 of aSAH had worse functional outcome (modified Rankin Scale (mRS) ≥ 3) upon 3-month follow-up [ 122 ].…”
Section: Sirs In Asahmentioning
confidence: 99%
“…The SIRS score, derived from the number of SIRS criteria met in terms of inflammatory activity [ 122 ], has been used to predict outcomes in septic and trauma patients [ 126 , 127 ]. Hokari et al found that patients with aSAH with a higher SIRS score on day 3 of aSAH had worse functional outcome (modified Rankin Scale (mRS) ≥ 3) upon 3-month follow-up [ 122 ].…”
Section: Sirs In Asahmentioning
confidence: 99%
“…The in-hospital mortality rate (12.5%) in this cohort of peritonitis patients is in the 10-20% range of peritonitis mortality generally reported in the sub-Saharan African region [25][26][27][28][29] but still higher than those reported in the western world [5,30]. The most likely explanation for this is the difference in the quality of the health care system…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, we found the PIPAS severity score tool to have a higher sensitivity than the qSOFA criteria although the latter tool is more specific. Several recent observational studies have also indicated that qSOFA criteria have low sensitivity but high specificity for identifying septic patients who are at high risk of mortality [18][19][20][21][22]25]. The implication of this in practice is that the use of the qSOFA criteria as the sole initial prognostic tool for potentially septic patients would miss out on a significant number of otherwise high-risk patients for sepsis-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…2 Systemic inflammatory response syndrome is not a specific response to sepsis but rather an adaptive response to several stressors triggering an increased oxygen demand, including but not limited to infection. 3 Among other conditions that activate SIRS are trauma, hypovolemia, emotional stress, and childbirth, and for this reason, SIRS has been criticized as overly sensitive for sepsis identification. 4 The SIRS response is a hypermetabolic state, activating the sympathetic nervous system and the innate immune system.…”
Section: The 1991 Sirs Paradigmmentioning
confidence: 99%